2010
DOI: 10.3920/978-90-8686-700-4
|View full text |Cite
|
Sign up to set email alerts
|

Single women, land and livelihood vulnerability in a communal area in Zimbabwe

Abstract: who shared their homes with my children and whose parents supported my family to ensure that my children continued to have a life while I worked on this thesis, ndinotenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 153 publications
(351 reference statements)
0
20
0
Order By: Relevance
“…The way women's land tenure experiences are conceived differently from those of men usually lead to the homogenization of women's land access and tenure security, because any time boundaries are drawn between men-and-women categories, borders are erased concerning the diversity that exists within women-and-women variations in land access and tenure security. Research findings from reputable organizations like the International Land Coalition and United States Agency for International Development indicate that there are large differences between women's participation in agricultural production and their ownership of agricultural land [8,9,60]. Many researchers, policymakers, and development practitioners tend not to acknowledge these differences in their works.…”
Section: Functional Differentiation Theory As a Path To Women's Empowmentioning
confidence: 99%
See 1 more Smart Citation
“…The way women's land tenure experiences are conceived differently from those of men usually lead to the homogenization of women's land access and tenure security, because any time boundaries are drawn between men-and-women categories, borders are erased concerning the diversity that exists within women-and-women variations in land access and tenure security. Research findings from reputable organizations like the International Land Coalition and United States Agency for International Development indicate that there are large differences between women's participation in agricultural production and their ownership of agricultural land [8,9,60]. Many researchers, policymakers, and development practitioners tend not to acknowledge these differences in their works.…”
Section: Functional Differentiation Theory As a Path To Women's Empowmentioning
confidence: 99%
“…A study of women's land rights vulnerability in Zimbabwe concluded that the role of patriarchy was sometimes overemphasised in studies of women's land rights vulnerability in the developing world [9]. Another study on Nigeria showed that the land challenges women face are sometimes as a result of "actions and inactions" of women [10].…”
Section: Introductionmentioning
confidence: 99%
“…The household responsibility system and social change in rural China, providing a longitudinal perspective by applying a cohort approach (Yuan, 2010). Single women, land and livelihood vulnerability in a communal area in Zimbabwe (Makura‐Paradza, 2010). …”
Section: A Comparative Application Of the Concept Of Householdmentioning
confidence: 99%
“…Single women, land and livelihood vulnerability in a communal area in Zimbabwe (Makura‐Paradza, 2010).…”
Section: A Comparative Application Of the Concept Of Householdmentioning
confidence: 99%
See 1 more Smart Citation